Les normes internationales à l’épreuve du local : les maires à Fukushima après l’accident nucléaire - Christine Fassert; Rina Kojima (Socio-anthropologie)
The environmental and health consequences of a nuclear accident are managed within an international normative and regulatory framework. This is the legacy of standardisation processes led by the International Atomic Energy Agency (IAEA) and the International Commission on Radiological Protection (ICRP), two organisations that have accompanied the development of this technoscience (Creager and Retetzi, 2019). Following the Fukushima nuclear accident in March 2011, the Japanese government deployed a nuclear accident management policy which aimed at promoting the rapid ‘reconstruction’ of the affected territories. This article is based on an eight-year longitudinal empirical survey conducted following the nuclear accident in the Fukushima Prefecture. It examines the administration of the accident’s consequences for the population, with a particular focus on the role of mayors. Drawing on the concepts of ‘habitability’ (Blanc, 2019) and ‘repair’ (Centemeri et al., 2020), we explore how mayors in two contaminated and evacuated villages manage the aftermath of the disaster. They must balance responding to the needs of their constituents within the confines of government policy while addressing the injustices caused by ‘zoning’ and associated financial compensation and restoring the landscape damaged by the nuclear accident. We examine how the normative framework developed by international nuclear institutions gives rise to challenging dilemmas for mayors and conflicts with many of the issues raised by residents concerning their living conditions post-disaster.